Pharmacodynamics, clinical findings and approval status of current and emerging tyrosine-kinase inhibitors for pancreatic neuroendocrine tumors. (2nd December 2019) - Fazio, Nicola; Cella, Chiara A.; Del Re, Marzia; Laffi, Alice; Rubino, Manila; Zagami, Paola; Spada, Francesca
ABSTRACT: Introduction : Pancreatic neuroendocrine tumors (panNETs) represent a rare group of malignancies. For decades, chemotherapy, somatostatin analogs and interferon represented the only systemic therapies; however, over the latest years, new options were registered, including Everolimus, Sunitinib (SUN), and Peptide Receptor Radionuclide Therapy. Areas covered : This review discusses the role of tyrosine kinase inhibitors (TKIs) in advanced panNETs. Expert opinion : TKIs showed an antiangiogenic and antiproliferative impact on advanced panNETs. Sunitinib is the only TKI currently available in clinical practice, having been approved on the basis of relevant results of a specific panNET phase III trial. New TKIs, such as Cabozantinib, Lenvatinib, Pazopanib, Surufatinib are still on investigation in panNETs. Although some phase II studies with the new TKIs yielded better PFS and RR compared with SUN, different study designs and tumor populations may have induced selection biases. However, it was reported that panNETs resistant to SUN could respond to a new TKI, indicating a possible further therapeutic line in this context. The global investigation plan of TKIs in panNETs is not homogeneous and it is difficult to understand what kind of development this can have in the near future for clinical practice.